O discurso sobre a história das Missões (RS): o caso do jornal O Nheçuano - Klein, Mirela Schröpfer (2021)
Based on the theoretical-methodological assumptions of Discourse Analysis carried out in Brazil today, this dissertation research focuses on how the about discourses, which circulate in relation to the history and in the “Missões” region of Rio Grande do Sul (RS), produce an institutionalized memory, which is, in our understanding, marked by the silencing of meanings and other memories. Thus, for the development of this study, we were interested in reflecting on how such ongoing discourse is constituted by a discursive memory, marked by silencing and affected by ideology. Considering the assumed theoretical affiliation, the analysis device that anchors this investigation is mainly constituted by notions of discourse, history, silencing policy and memory, which allowed us to explain the meaning effects of the object under analysis, namely: “O Nheçuano” newspaper – the “Missões” region circulation newspaper, which proposes to (re)tell the history of and about the “Missões”, especially in relation to the first phase of Jesuit missions implementation. Based on this object of study, from articles published in 42 editions of the newspaper, 24 discursive clippings were made, whose constitute our analytical research corpus. In view of this and our research objective, we understand that, when we reflect on these historical determinations that constitute the about discourse which circulates in the “Missões” region, we understand the effects of the dominant ideology is what determines such socio-historical context, as well as produces the silencing of other discourses, which, however, erupt on the discourse thread, returning to be remembered, as well as to produce meaning effects due to the discourse being marked by the discursive memory.